The RUFYs, a Family of Effector Proteins Involved in Intracellular Trafficking and Cytoskeleton Dynamics - Char, Rémy; Pierre, Philippe (Frontiers in Cell and Developmental Biology, 2020)
Intracellular trafficking is essential for cell structure and function. In order to perform key tasks such as phagocytosis, secretion or migration, cells must coordinate their intracellular trafficking and cytoskeleton dynamics. This relies on certain classes of proteins endowed with specialized and conserved domains that bridge membranes with effector proteins. Of particular interest are proteins capable of interacting with membrane subdomains enriched in specific phosphatidylinositol lipids, tightly regulated by various kinases and phosphatases. Here, we focus on the poorly studied RUFY family of adaptor proteins, characterized by a RUN domain, which interacts with small GTP-binding proteins, and a FYVE domain, involved in the recognition of phosphatidylinositol 3-phosphate. We report recent findings on this protein family that regulates endosomal trafficking, cell migration and upon dysfunction, can lead to severe pathology at the organismal level.